Propuesta de “ruta cultural – gastronómica montubia de jipijapa – la pila – montecristi - Landeta Bejarano, Zoraida Nathalie (2009)
In the tourism industry, there are new trends of tourism activities and have even developed new concepts which are in keeping with the contemporary reality of our days. Such is the case of community tourism, which focuses the participation or involvement of indigenous peoples who are in the area of influence from one sector to develop in the industry. The cultural route - gastronomic montubio of JipiJapa - La Pila - Montecristi, is a proposal that fits an entire community of people who have an ancestral identity that originates from the earliest pre-Columbian peoples who inhabited the coast of Ecuador to the present. But now unfortunately many of these people have been abandoning this identity due to migration of them to different cities and counties away. However, although there are some people "montubios" like oases in the desert who have these characteristics in the provinces mentioned above. The project proceeded to conduct a thorough investigation of the origins of identity montubio research using methods consistent with our objectives; this research indicates the result that most people who consider montubios agree with the proposal a route of this nature, others have found a favorable response in the aspect of tourism demand. Therefore we have obtained as a result, our hypothesis is valid because the proposed route may allow the rescue, strengthen and position the cultural heritage - Gourmet montubio community.